ANALISA PRESSURE BUILD UP DAN INTERFERENCE TEST PADA SUMUR ALPHA DAN “BETA LAPANGAN X - Arya Bintang Graha; Mulia Ginting; Edward Tobing (PROSIDING SEMINAR NASIONAL CENDEKIAWAN, 2015)
The main purpose of a hydrocarbon well test or pressure transient analysis is to determine the ability of a layer or the formation to produce. Transient pressure analysis is basically, to give balance pressure interference on the well tested. Result from this well testing is distinguishable become two functions, that is test to obtain reservoir character by executing pressure build-up test analysis and test to know communicating of flow unit by doing interferencetest with Stegmeier method method..